PENYULUHAN DAN PELATIHAN PENGGUNAAN LISTRIK HEMAT ENERGI DI LINGKUNGAN SMK NEGERI 1 CISARUA - Resa Pramudita; Neris Peri Ardiansyah; Muhammad Adli Rizqulloh; Wasimudin Surya Saputra; Ade Gafar Abdullah; Siscka Elvyanti; Hasbullah Hasbullah; Erik Haritman; Didin Wahyudin; Iwan Kustiawan; Agus Heri Setya Budi; Maman Somantri; Roer Eka Pawinanto (Universitas Widyatama, 2022)
The problem that underlies this activity is to see the condition of the school environment that requires counseling about the use of electrical equipment. The existence of teachers regarding the installation and maintenance of electrical installations in the regions is not well understood, very different from teachers who are in urban areas and moreover those with a background in electrical engineering vocational schools who are classified as advanced both in terms of knowledge level and skills in practice. On the basis of this condition guidance or counseling is carried out for these teachers. Even if they have the skills to install electrical installations, it is hoped that teachers will be able to maintain, repair and install electrical installations, even if they are simple ones. The method used in Community Service activities at SMK N 1 Cisarua, namely Lectures, discussions and exercises. The instructor explains material about the use of electronic devices followed by discussion and questions and answers, while the implementation can be carried out by the teaching team at each school who can consult with the lecturer about saving electricity. As a result of this counseling and training, teachers at SMK N 1 Cisarua can understand the importance of electrical energy and how to use electrical energy efficiently. The conclusion from this activity is that the teaching team at SMK N 1 Cisarua can save electricity in the school and its surroundings so as to reduce the cost of electrical energy.